Deficiency of Procollagen C-Proteinase Enhancer 1 in Mice has No Major Impact on Cardiac Collagen and Function Under Basal Conditions. Issue 5 (November 2021) - Sansilvestri-Morel, Patricia; Harouki-Crochemore, Najah; Bertin, Florence; Bertheux, Hélène; Vermeil de Conchard, Guy; Diguet, Nicolas; Desfosses, Emilie; Lecomte, Mathilde; Gonzalez, Arantxa; Diez, Javier; Tupinon-Mathieu, Isabelle; Delerive, Philippe
Abstract : Abstract: Maturation of fibrillar collagen is known to play a crucial role in the pathophysiology of myocardial fibrosis. Procollagen C-proteinase enhancer 1 (PCPE1) has a key role in procollagen maturation and collagen fibril formation. The phenotype of both male and female PCPE1 knock-out mice was investigated under basal conditions to explore the potential of PCPE1 as a therapeutic target in heart failure. Global constitutive PCPE1 −/− mice were generated. Serum procollagen I C-terminal propeptide, organ histology, and cutaneous wound healing were assessed in both wild type (WT) and PCPE1 −/− mice. In addition, the cardiac expression of genes involved in collagen metabolism was investigated and the total and insoluble cardiac collagen contents determined. Cardiac function was evaluated by echocardiography. No differences in survival, clinical chemistry, or organ histology were observed in PCPE1 −/− mice compared with WT. Serum procollagen I C-terminal propeptide was lower in PCPE1 −/− mice. Cardiac mRNA expression of Bmp1, Col1a1, Col3a1, and Loxl2 was similar, whereas Tgfb and Loxl1 mRNA levels were decreased in PCPE1 −/− mice compared with sex-matched WT. No modification of total or insoluble cardiac collagen content was observed between the 2 strains. Ejection fraction was slightly decreased in PCPE1 −/− male mice, but not in females. Finally, wound healing was not altered in PCPE1 −/− mice. PCPE1 deficiency does not trigger any major liabilities and does not affect cardiac collagen content nor its function under basal conditions. Further studies are required to evaluate its role under stressed conditions and determine its suitability as a therapeutic target for heart failure. Abstract : Supplemental Digital Content is Available in the Text.